Role of Social Media Health Influencers on Purchase Intention of Functional Beverages: Moderating Impact of Health Consciousness - Kumar, Satinder; Kaur, Bipinpreet; Goyal, Shavina (Information & Media, 2024)
As consumer interest in wellness and health continues to rise, functional beverages have gained popularity. However, the specific characteristics of social media health influencers (SMHIs) that affect consumers’ willingness to buy these products, particularly in relation to health consciousness, remain relatively unexplored. Motive of the study is to examine the influence of SMHIs on consumers’ intention to purchase functional beverages in the presence of health consciousness. Conceptual framework of the study was built upon the Social Learning Theory and the Theory of Planned Behaviour and the survey conducted in Northern India, involving 360 participants. The structural model analysis reveals noteworthy associations between the attributes of social media health influencers (namely, expertise, attractiveness, and trustworthiness) and consumers’ willingness to buy functional beverages. Moreover, study highlights that the impact of trustworthiness on purchase intention is moderated by the level of health consciousness among consumers. However, it was observed that health consciousness did not significantly moderate the relationship between expertise and attractiveness with purchase intention. Marketers can leverage the finding by strategically choosing influencers who possess desirable qualities, thereby increasing the persuasiveness and effectiveness of their promotional campaigns. Study reinforces the notion that consumers are highly influenced by the content and recommendations presented by influencers.
Keywords: Social Media Health Influencers; Purchase Intention; Trustworthiness; Attractiveness; Health Consciousness; Functional Beverages; Social Learning Theory